KESESUAIAN POLA DASAR LUCIA MORS DE CASTRO PADA BENTUK TUBUH WANITA IDEAL - Agusti, Riri; Zahri, Wildati; Nelmira, Weni (Journal of Home Economics and Tourism, 2015)
The basic pattern Lucia Mors De Castro came from Germany, which iscontained in Basic Pattern Making book. The basic pattern Lucia Mors De Castrohas never been used or investigated by the lacturer and students of KesejahteraanKeluarga FT UNP on the pattern of Indonesian women's clothing, especially for theideal female body shape. The purpose of this study is to describe a weakness, howto repair a weakness, and the suitability of basic pattern, sleves, and skirts of LuciaMors De Castro on the Indonesian ideal female body shape. The method of researchis applied research. The object of research is the basic pattern Lucia Mors De Castrowere tested on students Kesejateraan Keluarga ideal stature height of 165 cm,weight 55.25 cm, at the age of 22 years. Instrument of the research is the assessmentformat. Assessment carried out by 5 panelists are lecturers dressmaking fittingmanner. The analysis data technique used is descriptive statistics. The resultsshowed that the basic pattern Lucia Mors De Castro for the ideal body shape, hasseveral disadvantages including: 1) bust circumference looks loose, 2) waistcircumference looks loose, 3) bust depth appears to rise, 4) back height appears torise, 5) back width seems less appropriate, 6) armhole diameter look lessappropriate, 7) concave arm circumference seem cramped, 8) darts at the front ofthe skirt does not appropriate location, 9) darts rear skirt looks not appropriatelocation. Of research Lucia Mors De Castro can be adjusted to the ideal femalebody shape Indonesia, namely by doing some repairs on how to make a pattern.This can be seen from the results of the analysis of data on fitting to II, mode was 4,median was 4, and the percentage was 99,7.Kata kunci: Kesesuain pola dasar Lucia Mors De Castro, Wanita Indonesiabertubuh ideal.